When Gossips Meet : Women, Family, and Neighbourhood in Early Modern England. - Capp, Bernard (Oxford studies in social history., 2004)
This book explores how women of the poorer and middling sorts in early modern England sought to make the best of their lives in a society that excluded or marginalized them in almost every sphere. It argues that networks of close friends ('gossips') provided invaluable moral and practical support, helping them to shape their own lives and to play an active role in the affairs of the local community. - ;This book explores how women of the poorer and middling sorts in early modern England negotiated a patriarchal culture in which they were generally excluded, marginalized, or subordinated. It fo.